A Solution Management in Handling Economic Inequality Among Agrarian Communities - Sri Wahyuni Jamal; Suparno Suparno (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
Agriculture has been an inherent part of human civilization for centuries. Therefore, this study aims to analyze the relationship between agricultural production and agricultural community income. The pattern of their relationship followed the dynamics of the Lotka-Volterra model. Two of the six critical phenomena that might occur: first, if the farmer's crop were abundant, the farmers' income would increase rapidly; second, if the farmers' yields decreased, the farmer's income would automatically decrease. Low and unstable farmer income could lead to poor productivity and low economic growth. Thus, monitoring and early warning were essential to effectively prevent possible negative impacts on agricultural product production, consumption, and changes in market prices. Sustainable agricultural systems included maintenance or enhancement of environmental natural resources, food supply, and social welfare. In brief, good agricultural management could maintain the balance of the ecosystem, contribute to the economy continuously, and increase agrarian communities' economic resilience. Keywords: agrarian community; ecosystem; harvest cycle; income; Lotka-Volterra